Competitiveness and value added in Persian cucumber (Cucumis sativus L.) in contract farming: case study - Rebollar-Rebollar, Samuel; Ramírez-Abarca, Orsohe; Hernández-Martínez, Juvencio (REVISTA TERRA LATINOAMERICANA, 2022)
The Mexican cucumber is one of the main vegetables that generate foreign exchange for the country, since more than 90% of national production is exported to the United States of North America (USA) and generates a wide economic spill in the producing region, due to the jobs that demand. The objective was to quantify the prof itability and competitiveness of two greenhouses where Persian cucumbers are grown, one from the State of Mexico and the other from Morelos, which have a contract farming agreement with a commercial integrator. The Policy Analysis Matrix (MAP) was used at private prices. The results show that the cultivation of Persian cucumber in the larger greenhouse had a private prof itability coef f icient of (CRP) of 42% and the smaller one was 27%, while the private cost ratios (RCP) were 0.61 for the f irst and 0.71 for the second, conf irming that this type of cultivation, in the contract farming modality, is prof itable and competitive, with the greatest competitiveness being observed in the greenhouse with a larger surface area.